Clustering Analysis of Patchouli Plantations for Sustainable Patchouli Oil Supply Chain Using K-Means Algorithm - Maizi, Hazful; Sentia, Prima Denny; Ambartiasari, Geta; Erwan, Friesca (Journal of Applied Engineering and Technological Science (JAETS), 2025)
Growing demand for patchouli oil has undoubtedly become an opportunity for the patchouli industry, particularly in Aceh, which supplies about 80% of Indonesia’s patchouli oil in the global supply chain system. However, the opportunity is often misguided by farmers and even the government, which implements various programs related to patchouli cultivation without identifying the potential land that is suitable to be used for it. The condition indicated that not every land is suitable for patchouli cultivation. Thus, it is necessary to cluster the distribution of existing patchouli plantations. The clustering aims to identify the existing patchouli plantations that have the potential for replication. This study uses the K-Means method that combines variables (the planting land, the harvesting land, and total production) to provide information on the plantation’s potential scale in each region. The clustering measurement pointed out that the plantation in South Aceh Regency has the most potential land for sustainable cultivation, followed by several other areas included in Cluster 2 and Cluster 3. The study’s result is essential in contributing significantly to optimizing patchouli cultivation management sustainability to fulfill Aceh Province’s role as the best quality patchouli oil supplier.